Heart Signals: The Change of Relationship from Virtual to Reality in China - Wickelgren, Bruce F.; Stuart, Raquel A.; Lin, Yiheng; Sun, Jianing; Wu, Xinyun; Chen, Yinghui; Ding, Yixin; Yin, Jiahui; Wang, Sixian; Zhu, Yingying; Liu, Yuting; Yu, Shuting; et al. (Intercultural Communication Studies, 1970)
Heart Signals: The Change of Relationship from Virtual to Reality in China